Non-Enzymatic Amperometric Glucose Sensor Based on Carbon Nanodots and Copper Oxide Nanocomposites Electrode - Tharinee Sridara (Sensors, 2020)
In this research work, a non-enzymatic amperometric sensor for the determination of glucose was designed based on carbon nanodots (C-dots) and copper oxide (CuO) nanocomposites (CuO-C-dots). The CuO-C-dots nanocomposites were modified on the surface of a screen-printed carbon electrode (SPCE) to increase the sensitivity and selectivity of the glucose sensor. The as-synthesized materials were further analyzed for physico-chemical properties through characterization tools such as transmission electron microscopy (TEM) and Fourier-transform infrared spectroscopy (FTIR); and their electrochemical performance was also studied. The SPCE modified with CuO-C-dots possess desirable electrocatalytic properties for glucose oxidation in alkaline solutions. Moreover, the proposed sensing platform exhibited a linear range of 0.5 to 2 and 2 to 5 mM for glucose detection with high sensitivity (110 and 63.3 µA mM−1cm−2), and good selectivity and stability; and could potentially serve as an effective alternative method of glucose detection.